2011
DOI: 10.1179/143307511x13109310554562
|View full text |Cite
|
Sign up to set email alerts
|

High glass forming ability and good mechanical properties of Cu–Zr–Al bulk metallic glasses

Abstract: For developing bulk metallic glasses with high glass forming ability (GFA) and good mechanical properties, Cu 922x Zr x Al 8 (x535-65 at-%) alloys have been studied by means of tilt mould casting method. The largest glassy rod with a critical diameter of 18 mm in this alloy series was obtained for Cu 42 Zr 50 Al 8 alloy. The Hruby factor is appropriate for evaluating GFA in the cast Zr-Cu-Al bulk glassy alloy. The bulk metallic glasses with high GFA exhibit good mechanical properties, i.e. compressive fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…However, we can see that the highest T g is observed for the Cu 44 Zr 52 Al 4 and Cu 40 Zr 47 Al 13 , indicating that, within the same cooling rate, these alloys form glassy state before the Cu 42 Zr 50 Al 8 alloy. This is inconsistent with the experimental study of Zhou et al [ 28 ] who showed on the basis of an examination of GFA and mechanical properties of Cu 92– x Zr x Al 8 ( x = 35–65 at%) alloys that the best glass former is Cu 42 Zr 50 Al 8 with a unique combination of mechanical properties including elastic Young's modulus of 90–123 GPa, compressive fracture strength of almost 1783–2240 MPa, and finally plastic strain ranging from 0 to 0.73%.…”
Section: Resultscontrasting
confidence: 99%
“…However, we can see that the highest T g is observed for the Cu 44 Zr 52 Al 4 and Cu 40 Zr 47 Al 13 , indicating that, within the same cooling rate, these alloys form glassy state before the Cu 42 Zr 50 Al 8 alloy. This is inconsistent with the experimental study of Zhou et al [ 28 ] who showed on the basis of an examination of GFA and mechanical properties of Cu 92– x Zr x Al 8 ( x = 35–65 at%) alloys that the best glass former is Cu 42 Zr 50 Al 8 with a unique combination of mechanical properties including elastic Young's modulus of 90–123 GPa, compressive fracture strength of almost 1783–2240 MPa, and finally plastic strain ranging from 0 to 0.73%.…”
Section: Resultscontrasting
confidence: 99%